Effect of spinal manipulation on shoulder pain and range of motion in individuals with rotator cuff tendinopathy - Silva, Alyssa Conte da; Padilha, Juliana Falcão; Marques, Jefferson Luiz Brum; Marques, Cláudia Mirian de Godoy (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: There are few studies that propose to identify the relations of the spinal manipulation on the pain and the mobility of the shoulder, especially in injuries of the rotator cuff. Objective: To analyze the effect of spinal manipulation on shoulder pain and range of motion in individuals with rotator cuff tendinopathy. Method: Quasi-experimental study with quantitative approach. The sample consisted of volunteers aged between 20 and 70 years, presenting pain for at least 6 months, with Rotator Cuff Tendinopathy (RCT). An evaluation form composed of the identification data was applied. Subsequently, the following evaluations were performed: kinetic-functional, pain through the Visual Analogue Scale (VAS) and Range of Motion (ROM) of the shoulder (flexion and abduction) using the goniometer. After the evaluations, the spinal manipulation (“Crossed Pisiform”) was performed on the thoracic spine, and then ROM and pain were evaluated. Statistical analysis showed the normality of the data by the Shapiro-Wilk test, comparing the effect of pre and post manipulation. A paired t-test was applied, adopting significance level of 5%. Results: Pain after spinal manipulation presented a significant reduction (p=0,019). The flexion movement after manipulation showed an increase in ROM in the shoulder with injury, but not significant (p=0,058), and for the abduction movement a significant increase was registered in both the shoulder with injury (p=0,01) and without injury (p=0,03). Conclusion: After spinal manipulation it was possible to verify decrease of shoulder pain as well as increase of shoulder ROM with and without injury in the abduction movement.